Institutional environment in North Korea: market structure and overcoming institutional voids - Jylhä, Hanne-Lotte (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
The research was sparked by an exchange in South Korea, as the author identified a gap in research that provides economic, up to date and realistic information about the North Korean market in English language. A need for a research was identified that would describe the market’s existing and missing market structures and explore possibilities to overcome the missing market structures. Institutional theory was chosen as a suitable framework to describe and explore the market. The research question was formulated as follows: “How can foreign companies overcome institutional voids in the North Korean market?”. To answer the research question, it was divided into three sub-questions as follows: (1) What is the institutional environment in North Korea like? (2) What are the major institutional voids in the North Korean market? (3) What possibilities do foreign companies have to overcome institutional voids? The research is qualitative by nature due to the descriptive and exploratory nature of the research question. Data collection consisted of expert interview and content analysis, resulting in primary data of two interviews and secondary data of 95 articles from 40 different sources. The data was analyzed with the systematical technique of content analysis. The data was coded, classified and presented as concepts with the help of a classification system that was build following the theoretical framework adapted for this study. The findings can be summarized as follows. (1) The market institutions are characterized by an overlapping dual system of formal, socialist structures and informal, market-oriented structures. (2) Institutional voids prevail on both the market’s contextual and on the market level. They are partly result of old institutions being replaced by new institutions that lack institutionalization. (3) Identified possibilities to overcome institutional voids correspond with possibilities drawn from previous research. This decreases the image of North Korea as an impossibly unique market to operate in. (4) Emerging middle class, rapidly growing entrepreneurial activities and women’s increasing role in business drive a down-to-up change in the market. This signals the recent development of the market, yet has been overlooked in the Western media. Thus there is a need for further economic, up to date research concerning North Korea.